Positive electrode active material composition, aqueous positive electrode slurry, positive electrode sheet, secondary battery, and power using device

CN116565153BActive Publication Date: 2026-10-20CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202210099465.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-01-27
Publication Date
2026-10-20
Estimated Expiration
2042-01-27

AI Technical Summary

Technical Problem

正极极片是决定二次电池性能的关键因素之一,用于现有正极浆料的溶剂通常为油系溶剂,例如N-甲基吡咯烷酮(NMP),但是NMP存在用量高、易挥发、毒性高且成本高的缺陷,不仅会对环境造成严重污染,而且还会危害人的身体健康

Benefits of technology

[0025]本申请第四方面提供一种二次电池,包括本申请第三方面的正极极片。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116565153B_ABST
    Figure CN116565153B_ABST
Patent Text Reader

Abstract

The application discloses a positive electrode active material composition, an aqueous positive electrode slurry, a positive electrode sheet, a secondary battery and an electric device. The positive electrode active material composition comprises a first positive electrode active material, a second positive electrode active material and a third positive electrode active material. The volume average particle size Dv50 of the first positive electrode active material is A1 mu m, 0.2 <= A1 <= 0.8; the volume average particle size Dv50 of the second positive electrode active material is A2 mu m, 1.0 <= A2 <= 2.5; and the volume average particle size Dv50 of the third positive electrode active material is A3 mu m, 3.0 <= A3 <= 6.0. The application can make the positive electrode sheet have a higher compaction density and also have a lower moisture content.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of battery technology, and particularly relates to a positive electrode active material composition, an aqueous positive electrode slurry, a positive electrode sheet, a secondary battery, and an electrical device. Background Technology

[0002] In recent years, secondary batteries have been widely used in energy storage power systems such as hydropower, thermal power, wind power, and solar power plants, as well as in power tools, electric bicycles, electric motorcycles, electric cars, military equipment, aerospace, and many other fields. With the application and promotion of secondary batteries, their cost and environmental pollution issues have received increasing attention. The positive electrode is one of the key factors determining the performance of a secondary battery. The solvents used in existing positive electrode slurries are usually oil-based solvents, such as N-methylpyrrolidone (NMP). However, NMP has drawbacks such as high usage, high volatility, high toxicity, and high cost, which not only cause serious environmental pollution but also harm human health. Therefore, it is necessary to develop a low-cost, environmentally friendly, and high-performance aqueous positive electrode slurry. Summary of the Invention

[0003] The purpose of this application is to provide a positive electrode active material composition, an aqueous positive electrode slurry, a positive electrode sheet, a secondary battery, and an electrical device, which aims to enable the positive electrode sheet to have a high compaction density while having a low moisture content, so that the secondary battery can simultaneously achieve high safety performance, high energy density, and good electrochemical performance.

[0004] The first aspect of this application provides a positive electrode active material composition, comprising a first positive electrode active material, a second positive electrode active material, and a third positive electrode active material, wherein the volume average particle size Dv50 of the first positive electrode active material is A1 μm, 0.2≤A1≤0.8; the volume average particle size Dv50 of the second positive electrode active material is A2 μm, 1.0≤A2≤2.5; and the volume average particle size Dv50 of the third positive electrode active material is A3 μm, 3.0≤A3≤6.0.

[0005] The inventors of this application unexpectedly discovered during their research that combining three positive electrode active materials with different particle sizes and applying them to the positive electrode sheet can significantly reduce the moisture content of the positive electrode sheet while increasing its compaction density. Furthermore, the resulting battery can simultaneously achieve high safety performance, high energy density, and good electrochemical performance. Although the mechanism is not yet clear, the inventors speculate that the possible reason is that by combining a first, second, and third positive electrode active material with different particle sizes, a synergistic effect is formed among the three positive electrode active materials.

[0006] In any embodiment of this application, 4 ≤ A3 / A1 ≤ 20, and optionally, 5 ≤ A3 / A1 ≤ 15. When A3 / A1 is within a suitable range, the synergistic effect between the third positive electrode active material and the first positive electrode active material can be better utilized, enabling the third positive electrode active material to effectively reduce the densely packed state formed by the first positive electrode active material. As a result, the positive electrode sheet can have a higher compaction density while having a lower moisture content, and the positive electrode sheet also has good ion and electron transport performance.

[0007] In any embodiment of this application, 1.6 ≤ A3 / A2 ≤ 6.0, and optionally, 2.0 ≤ A3 / A2 ≤ 4.0. When A3 / A2 is within a suitable range, the synergistic effect between the third positive electrode active material and the second positive electrode active material can be better utilized, as well as the regulating and lubricating effect of the second positive electrode active material can be fully utilized. Therefore, the positive electrode sheet can have a high compaction density while having a lower moisture content, and the positive electrode sheet also has good ion and electron transport performance.

[0008] In any embodiment of this application, 1.5 ≤ A2 / A1 ≤ 7.5, and optionally, 1.8 ≤ A2 / A1 ≤ 6.5. When A2 / A1 is within a suitable range, the synergistic effect between the second positive electrode active material and the first positive electrode active material can be better utilized, as well as the regulating and lubricating effect of the second positive electrode active material can be fully utilized. Therefore, the positive electrode sheet can have a high compaction density while having a lower moisture content, and the positive electrode sheet also has good ion and electron transport performance.

[0009] In any embodiment of this application, based on the total mass of the positive electrode active material composition being 100%, the mass percentage w1 of the first positive electrode active material is 60%-80%, the mass percentage w2 of the second positive electrode active material is 10%-40%, and the mass percentage w3 of the third positive electrode active material is 7%-15%. In this case, the positive electrode sheet can have a high compaction density while having a lower moisture content, and the positive electrode sheet also has good ion and electron transport properties.

[0010] In any embodiment of this application, 5 ≤ w1 / w3 ≤ 11, and optionally, 6 ≤ w1 / w3 ≤ 9. When w1 / w3 is within a suitable range, the synergistic effect between the third positive electrode active material and the first positive electrode active material can be better utilized. Therefore, the positive electrode sheet can have a higher compaction density while having a lower moisture content, and the positive electrode sheet also has good ion and electron transport performance.

[0011] In any embodiment of this application, the first positive electrode active material, the second positive electrode active material, and the third positive electrode active material each independently include at least one of lithium iron phosphate, lithium manganese phosphate, lithium cobalt phosphate, lithium iron manganese phosphate, lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and their respective modified compounds. Optionally, the first positive electrode active material, the second positive electrode active material, and the third positive electrode active material each independently include at least one of lithium iron phosphate, lithium manganese phosphate, lithium cobalt phosphate, lithium iron manganese phosphate, and their respective modified compounds.

[0012] In any embodiment of this application, the first positive electrode active material, the second positive electrode active material, and the third positive electrode active material are made of the same material.

[0013] In any embodiment of this application, a conductive carbon layer is disposed on the surface of the first positive electrode active material.

[0014] In any embodiment of this application, a conductive carbon layer is disposed on the surface of the second positive electrode active material.

[0015] In any embodiment of this application, a conductive carbon layer is disposed on the surface of the third positive electrode active material.

[0016] In any embodiment of this application, the first positive electrode active material mainly comprises a primary particle structure.

[0017] In any embodiment of this application, the second positive electrode active material mainly comprises a primary particle structure.

[0018] In any embodiment of this application, the third positive electrode active material mainly comprises a secondary particle structure.

[0019] A second aspect of this application provides an aqueous positive electrode slurry, comprising a solid component and a solvent water, wherein the solid component comprises an aqueous binder and a positive electrode active material composition of the first aspect of this application.

[0020] In any embodiment of this application, the water-based adhesive includes at least one of acrylonitrile copolymer, polyethyleneimine, polyacrylic acid, polymethacrylic acid, polyacrylamide, polyethylene oxide, polyvinyl alcohol, sodium alginate, carboxymethyl chitosan, and sodium carboxymethyl cellulose.

[0021] A third aspect of this application provides a positive electrode sheet, including a positive current collector and a positive electrode film layer disposed on the positive current collector, wherein the positive electrode film layer includes an aqueous binder and a positive electrode active material composition of the first aspect of this application, or the positive electrode film layer is formed by drying an aqueous positive electrode slurry of the second aspect of this application.

[0022] The positive electrode sheet of this application can have a high compaction density while having a low moisture content. The positive electrode sheet of this application can also have good ion and electron transport performance, so the battery assembled from it can simultaneously achieve high safety performance, high energy density and good electrochemical performance.

[0023] In any embodiment of this application, in the scanning electron microscope cross-sectional image of the positive electrode film layer, the longest diagonal length of the first positive electrode active material particle is a1 μm, 0.2≤a1≤1.2, and the average center-to-center distance between adjacent first positive electrode active material particles is L1 μm, 0≤L1≤1.0; the longest diagonal length of the second positive electrode active material particle is a2 μm, 1.5≤a2≤2.7, and the average center-to-center distance between adjacent second positive electrode active material particles is L2 μm, 0.5≤L2≤2.5; the longest diagonal length of the third positive electrode active material particle is a3 μm, 3.2≤a3≤8.0, and the average center-to-center distance between adjacent third positive electrode active material particles is L3 μm, 5.0≤L3≤80.0.

[0024] In any embodiment of this application, the compaction density of the positive electrode sheet is ≥2.50 g / cm³. 3 Furthermore, the moisture content after vacuum drying at 90°C for 6 hours is ≤400ppm. Optionally, the moisture content of the positive electrode sheet after vacuum drying at 90°C for 6 hours is ≤365ppm.

[0025] The fourth aspect of this application provides a secondary battery, including the positive electrode sheet of the third aspect of this application.

[0026] The fifth aspect of this application provides an electrical device, including the secondary battery of the fourth aspect of this application.

[0027] The secondary battery of this application comprises a positive electrode active material composition formed by combining a first positive electrode active material, a second positive electrode active material, and a third positive electrode active material with different particle sizes. The three positive electrode active materials with different particle sizes can form a synergistic effect, enabling the positive electrode sheet to have both high compaction density and low moisture content, and also giving the positive electrode sheet good ion and electron transport performance. Therefore, the secondary battery of this application can simultaneously achieve high safety performance, high energy density, and good electrochemical performance. The electrical device of this application includes the secondary battery provided in this application, and thus has at least the same advantages as the secondary battery. Attached Figure Description

[0028] To more clearly illustrate the technical solutions of the embodiments of this application, the accompanying drawings used in the embodiments of this application will be briefly described below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on the drawings without creative effort.

[0029] Figure 1 This is a schematic diagram of one embodiment of the secondary battery of this application.

[0030] Figure 2 yes Figure 1 An exploded view of the implementation method of the secondary battery.

[0031] Figure 3 This is a schematic diagram of one embodiment of the battery module of this application.

[0032] Figure 4 This is a schematic diagram of one embodiment of the battery pack of this application.

[0033] Figure 5 yes Figure 4 An exploded view of an embodiment of the battery pack shown.

[0034] Figure 6 This is a schematic diagram of one embodiment of an electrical device that uses a secondary battery as a power source, as described in this application.

[0035] Figure 7 and Figure 8 These are cross-sectional images of the positive electrode film layer of Example 1 under scanning electron microscope at different magnifications. Detailed Implementation

[0036] The following detailed description, with appropriate reference to the accompanying drawings, discloses embodiments of the positive electrode active material composition, aqueous positive electrode slurry, positive electrode sheet, secondary battery, and power application device of this application. However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repetitive descriptions of practically identical structures may be omitted. This is to avoid unnecessarily lengthy descriptions and to facilitate understanding by those skilled in the art. Furthermore, the accompanying drawings and the following description are provided for the purpose of enabling those skilled in the art to fully understand this application and are not intended to limit the subject matter of the claims.

[0037] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is expected that ranges of 60-110 and 80-120 are also included. Furthermore, if minimum range values ​​of 1 and 2 are listed, and if maximum range values ​​of 3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0038] Unless otherwise specified, all embodiments and optional embodiments of this application may be combined with each other to form new technical solutions, and such technical solutions should be considered to be included in the disclosure of this application.

[0039] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions, and such technical solutions shall be deemed to be included in the disclosure of this application.

[0040] Unless otherwise specified, all steps in this application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.

[0041] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.

[0042] Unless otherwise specified, the term "or" is inclusive in this application. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, the condition "A or B" is satisfied by any of the following conditions: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0043] A secondary battery, also known as a rechargeable battery or accumulator, is a battery that can be recharged after discharge to reactivate its active materials and continue to be used. Typically, a secondary battery includes a positive electrode, a negative electrode, an electrolyte, and a separator. During charging and discharging, active ions repeatedly insert and extract between the positive and negative electrodes. The separator, located between the positive and negative electrodes, primarily prevents short circuits while allowing active ions to pass through. The electrolyte, situated between the positive and negative electrodes, conducts the active ions.

[0044] With the application and promotion of secondary batteries, their cost and environmental pollution issues have received increasing attention. Aqueous cathode slurries have attracted growing attention from researchers due to their low cost and environmental friendliness. However, aqueous cathode slurries have poor fluidity and are difficult to disperse, resulting in cathode sheets with high moisture content, low compaction density, poor flexibility, and difficulty in winding.

[0045] In view of this, the inventors of this application, through extensive research and practice, have proposed a composition of positive electrode active materials suitable for use in aqueous positive electrode slurries and positive electrode sheets.

[0046] Positive electrode active material composition

[0047] The first aspect of this application provides a positive electrode active material composition, including a first positive electrode active material, a second positive electrode active material, and a third positive electrode active material. The first positive electrode active material has a volume average particle size Dv50 of A1 μm, where 0.2 ≤ A1 ≤ 0.8; the second positive electrode active material has a volume average particle size Dv50 of A2 μm, where 1.0 ≤ A2 ≤ 2.5; and the third positive electrode active material has a volume average particle size Dv50 of A3 μm, where 3.0 ≤ A3 ≤ 6.0.

[0048] Aqueous cathode slurries often use aqueous binders with hydrophilic groups (such as polyacrylic acid). These hydrophilic groups and the solvent water can significantly impact the performance of secondary batteries. For example, some moisture may remain in the cathode sheet and is difficult to remove completely. After the cathode sheet is assembled into a battery, this moisture can react with the electrolyte and electrode active materials inside the battery, not only consuming active ions and causing a decrease in battery energy density and rapid capacity decay, but also causing battery swelling and increasing safety risks. Therefore, effective technical means are needed to reduce the impact of moisture on battery performance.

[0049] The main strategies adopted by existing technologies to improve the performance of aqueous cathode slurries are to optimize the molecular structure of aqueous binders and optimize the slurry preparation process. However, existing technologies rarely consider the impact of cathode active materials on the performance of aqueous cathode slurries.

[0050] Compared to existing cathode sheets prepared using oil-based cathode slurries, cathode sheets prepared using aqueous cathode slurries suffer from lower compaction density, making it difficult for assembled batteries to achieve high energy density. Furthermore, existing cathode sheets often suffer from a trade-off between compaction density and moisture content; for example, reducing the moisture content of the cathode sheet will decrease its compaction density, and increasing the compaction density will increase its moisture content. Consequently, it is difficult for batteries to simultaneously achieve high energy density and good electrochemical performance.

[0051] The inventors of this application unexpectedly discovered during their research that combining three positive electrode active materials with different particle sizes and applying them to the positive electrode sheet can significantly reduce the moisture content of the positive electrode sheet while increasing its compaction density. This reduces the side reactions between moisture and the electrolyte and electrode active materials, thereby enabling the battery to simultaneously achieve high safety performance, high energy density, and good electrochemical performance.

[0052] The third positive electrode active material has relatively large particles, with a Dv50 between 3.0 μm and 6.0 μm. This size offers several advantages: it facilitates the formation of more interparticle voids, increasing the evaporation channels for moisture in the slurry coating and thus reducing the moisture content of the positive electrode sheet; it also helps reduce the bound water content on the particle surface, further lowering the moisture content of the positive electrode sheet. However, when used alone, the third positive electrode active material is difficult to form a densely packed state, resulting in a lower compaction density of the positive electrode sheet, which is detrimental to improving the energy density of the secondary battery. Furthermore, a lower compaction density of the positive electrode sheet results in a smaller contact area between the positive electrode active material particles, fewer electron conduction channels, higher internal resistance, and consequently, a decrease in the rate performance of the secondary battery.

[0053] The first positive electrode active material has relatively small particles, with a Dv50 between 0.2 μm and 0.8 μm. This allows for a densely packed state, resulting in a high bulk density and thus a high compaction density for the positive electrode sheet. However, the first positive electrode active material often has a high specific surface area and a high bound water content on the particle surface. Simultaneously, the dense packing of the first positive electrode active material reduces the number of water evaporation channels in the slurry coating. Furthermore, the excessively high compaction density of the positive electrode sheet, with its small particle spacing and tight contact, further reduces the active ion transport channels, hindering battery capacity. Therefore, when used alone, the first positive electrode active material is not conducive to water removal from the slurry coating, resulting in a positive electrode sheet with high moisture content and poor active ion transport performance. Consequently, the resulting battery struggles to simultaneously achieve both high energy density and good electrochemical performance.

[0054] The particle size of the second positive electrode active material is between that of the first and third positive electrode active materials, with a Dv50 between 1.0 μm and 2.5 μm. This allows for a relatively dense filling state, resulting in a high compaction density for the positive electrode sheet. However, this dense filling also reduces the number of moisture evaporation channels in the slurry coating. Furthermore, the smaller spacing and tighter contact between the particles of the second positive electrode active material further reduces the number of active ion transport channels, hindering battery capacity development. Therefore, when used alone, the second positive electrode active material is not conducive to moisture removal from the slurry coating, resulting in a positive electrode sheet with high moisture content and poor active ion transport performance. Consequently, the resulting battery struggles to simultaneously achieve both high energy density and good electrochemical performance.

[0055] Therefore, when the first, second, and third positive electrode active materials are used individually, none of them can achieve both high compaction density and low moisture content in the positive electrode sheet. Consequently, the resulting battery also struggles to simultaneously achieve both high energy density and good electrochemical performance.

[0056] Therefore, although the mechanism is not yet clear, the inventors of this application speculate that the possible reason is that by combining a first positive electrode active material, a second positive electrode active material and a third positive electrode active material with different particle sizes, a synergistic effect is formed among the three positive electrode active materials with different particle sizes. As a result, the positive electrode sheet has both high compaction density and low moisture content, and the positive electrode sheet also has good ion and electron transport performance. The battery obtained by this can simultaneously achieve high safety performance, high energy density and good electrochemical performance.

[0057] First, the third positive electrode active material can form more interparticle voids, increasing the water evaporation channels. Second, during the slurry coating compaction process, the smaller-sized first positive electrode active material is easily squeezed into the interparticle voids, increasing the compaction density of the positive electrode sheet. Third, the particle size of the second positive electrode active material is between that of the first and third positive electrode active materials, which can play an adjusting and lubricating role. On the one hand, it adjusts the first and third positive electrode active materials to form a suitable packing state, thereby ensuring that the slurry coating has more water evaporation channels; on the other hand, it acts as a lubricant during the slurry coating compaction process. The first positive electrode active material, with its smaller size, can better slide and fill the gaps between particles, increasing the compaction density of the positive electrode sheet. Fourth, the large size difference between the first and third positive electrode active materials makes it difficult for them to slide. The second positive electrode active material can coordinate the sliding effect between the particles of the first and third positive electrode active materials. Therefore, when water evaporates and forms voids in the slurry coating, the third positive electrode active material can more easily collapse under gravity and fill the voids. This also reduces the number of cracks caused by the void effect of water evaporation during the drying process of the slurry coating. Therefore, the slurry coating formed using the positive electrode active material composition of this application can have a high compaction density while also having suitable water evaporation channels, facilitating water discharge. Consequently, the positive electrode sheet has a high compaction density and a low moisture content, and also exhibits good ion and electron transport properties.

[0058] Furthermore, due to the significant size difference between the first and third positive electrode active materials, when only the first and third positive electrode active materials are used in a composition, the third positive electrode active material cannot effectively reduce the packing density of the first positive electrode active material. Consequently, the moisture evaporation channels in the slurry coating are insufficient, which is detrimental to effectively reducing the moisture content of the positive electrode sheet. Because the particle size difference between the second and third positive electrode active materials is relatively small, when only the second and third positive electrode active materials are used in a composition, it is difficult to form a dense filling state, resulting in a low particle packing density and consequently a low compaction density of the positive electrode sheet. Because both the first and second positive electrode active materials have small particle sizes, when only the first and second positive electrode active materials are used in a composition, the second positive electrode active material cannot effectively reduce the dense filling state formed by the first positive electrode active material. Consequently, the moisture evaporation channels in the slurry coating are insufficient, which is detrimental to effectively reducing the moisture content of the positive electrode sheet. Therefore, even when any two of the first, second, and third positive electrode active materials are combined, it is still impossible to achieve both high compaction density and low moisture content in the positive electrode sheet. Furthermore, the resulting battery is unlikely to simultaneously achieve both high energy density and good electrochemical performance.

[0059] In the positive electrode active material composition of this application, a large difference in particle size between the third positive electrode active material and the first positive electrode active material may affect the drainage effect of the slurry coating. In some embodiments, 4≤A3 / A1≤20. Optionally, 4≤A3 / A1≤18, 4≤A3 / A1≤15, 4≤A3 / A1≤10, 5≤A3 / A1≤18, 5≤A3 / A1≤15, or 5≤A3 / A1≤10. When the ratio A3 / A1 of the particle size of the third positive electrode active material to that of the first positive electrode active material is within a suitable range, the synergistic effect between the third and first positive electrode active materials can be better utilized, allowing the third positive electrode active material to effectively reduce the densely packed state formed by the first positive electrode active material. Consequently, the positive electrode sheet can have a higher compaction density while having a lower moisture content, and the positive electrode sheet also has good ion and electron transport performance.

[0060] In the positive electrode active material composition of this application, when the particle size difference between the third positive electrode active material and the second positive electrode active material is small, it may affect the drainage effect of the slurry coating. In some embodiments, 1.6 ≤ A3 / A2 ≤ 6.0. Optionally, 1.6≤A3 / A2≤5.5, 1.6≤A3 / A2≤5.0, 1.6≤A3 / A2≤4.5, 1.6≤A3 / A2≤4.0, 2.0≤A3 / A2≤6.0, 2.0≤A3 / A2≤5.5, 2.0≤A3 / A2≤5.0, 2.0≤A3 / A2≤4.5, 2.0≤A3 / A2≤4.0, 2.5≤A3 / A2≤6.0, 2.5≤A3 / A2≤5.5, 2.5≤A3 / A2≤5.0, 2.5≤A3 / A2≤4.5, or 2.5≤A3 / A2≤4.0. When the ratio A3 / A2 of the particle size of the third positive electrode active material to that of the second positive electrode active material is within a suitable range, the synergistic effect between the third and second positive electrode active materials can be better utilized, as well as the regulating and lubricating effect of the second positive electrode active material can be fully utilized. Therefore, the positive electrode sheet can have a higher compaction density while having a lower moisture content, and the positive electrode sheet also has good ion and electron transport performance.

[0061] In the positive electrode active material composition of this application, when the particle size difference between the second positive electrode active material and the first positive electrode active material is large, it may affect the drainage effect of the slurry coating. In some embodiments, 1.5≤A2 / A1≤7.5. Optionally, 1.5≤A2 / A1≤6.5, 1.5≤A2 / A1≤5.0, 1.5≤A2 / A1≤4.0, 1.8≤A2 / A1≤6.5, 1.8≤A2 / A1≤5.0, 1.8≤A2 / A1≤4.0, 2.0≤A2 / A1≤6.5, 2.0≤A2 / A1≤5.0, 2.0≤A2 / A1≤4.0, 2.5≤A2 / A1≤6.5, 2.5≤A2 / A1≤5.0, or 2.5≤A2 / A1≤4.0. When the ratio A2 / A1 of the particle size of the second positive electrode active material to that of the first positive electrode active material is within a suitable range, the synergistic effect between the second and first positive electrode active materials can be better utilized, as well as the regulating and lubricating effect of the second positive electrode active material can be fully utilized. Therefore, the positive electrode sheet can have a higher compaction density while having a lower moisture content, and the positive electrode sheet also has good ion and electron transport performance.

[0062] In some embodiments, 5 ≤ A3 / A1 ≤ 15 and 2.0 ≤ A3 / A2 ≤ 4.0. Optionally, 5 ≤ A3 / A1 ≤ 15, 2.0 ≤ A3 / A2 ≤ 4.0, and 1.8 ≤ A2 / A1 ≤ 6.5. In this case, the synergistic effect between the first, second, and third positive electrode active materials can be better utilized, thus the positive electrode sheet can have a higher compaction density while having a lower moisture content.

[0063] In some embodiments, based on the total mass of the positive electrode active material composition being 100%, the mass percentage w1 of the first positive electrode active material is 60%-80%, the mass percentage w2 of the second positive electrode active material is 10%-40%, and the mass percentage w3 of the third positive electrode active material is 7%-15%.

[0064] By rationally combining the contents of first, second, and third positive electrode active materials with different particle sizes, the slurry coating can exhibit a localized distribution of small particles surrounding larger particles. In this state, on the one hand, the second positive electrode active material can better regulate the first and third positive electrode active materials, ensuring a suitable packing state and guaranteeing the slurry coating has numerous moisture evaporation channels; on the other hand, during the slurry coating compaction process, the smaller-sized first positive electrode active material can better slide and fill the gaps between particles, increasing the compaction density of the positive electrode sheet. Therefore, the positive electrode sheet can have a high compaction density while maintaining a low moisture content, and it also possesses excellent ion and electron transport properties.

[0065] In the positive electrode active material composition of this application, when the content of the first positive electrode active material differs significantly from that of the third positive electrode active material, the third positive electrode active material cannot effectively reduce the densely packed state formed by the first positive electrode active material, resulting in insufficient water evaporation channels in the slurry coating, which may affect the drainage effect of the slurry coating. When the content of the first positive electrode active material differs significantly from that of the third positive electrode active material, the high packing density of the first positive electrode active material cannot be fully utilized, which is not conducive to obtaining a positive electrode sheet with a high compaction density. In some embodiments, 5≤w1 / w3≤11. Optionally, 5.5≤w1 / w3≤11, 6≤w1 / w3≤11, 6.4≤w1 / w3≤11, 7≤w1 / w3≤11, 7.5≤w1 / w3≤11, 5.5≤w1 / w3≤9, 6≤w1 / w3≤9, 6.4≤w1 / w3≤9, 7≤w1 / w3≤9, or 7.5≤w1 / w3≤9. When the ratio w1 / w3 of the content of the first positive electrode active material to the content of the third positive electrode active material is within a suitable range, the synergistic effect between the third positive electrode active material and the first positive electrode active material can be better exerted. Therefore, the positive electrode sheet can have a higher compaction density and a lower moisture content, and the positive electrode sheet also has good ion and electron transport performance.

[0066] In the positive electrode active material composition of this application, the first positive electrode active material, the second positive electrode active material, and the third positive electrode active material are all materials capable of extracting and inserting lithium ions. In some embodiments, the first positive electrode active material, the second positive electrode active material, and the third positive electrode active material each independently include at least one of lithium transition metal oxide, lithium-containing phosphate with an olivine structure, and their respective modified compounds.

[0067] As an example, the first, second, and third positive electrode active materials each independently include at least one of lithium iron phosphate, lithium manganese phosphate, lithium cobalt phosphate, lithium iron manganese phosphate, lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and their respective modified compounds. Optionally, the first, second, and third positive electrode active materials each independently include at least one of lithium iron phosphate, lithium manganese phosphate, lithium cobalt phosphate, lithium iron manganese phosphate, and their respective modified compounds.

[0068] In some embodiments, the first positive electrode active material, the second positive electrode active material, and the third positive electrode active material may be made of the same material.

[0069] Optionally, the first, second, and third positive electrode active materials are all lithium phosphates with an olivine structure and their modified compounds. Further, the first, second, and third positive electrode active materials are all at least one of lithium iron phosphate, lithium manganese phosphate, lithium cobalt phosphate, lithium iron manganese phosphate, and their respective modified compounds.

[0070] In this application, the modifying compounds for the aforementioned positive electrode active materials can be those that modify the positive electrode active materials by doping, surface coating, or simultaneous doping and coating. In some embodiments, a conductive carbon layer may be disposed on the surface of the first positive electrode active material. In some embodiments, a conductive carbon layer may be disposed on the surface of the second positive electrode active material. In some embodiments, a conductive carbon layer may be disposed on the surface of the third positive electrode active material.

[0071] In some embodiments, the first positive electrode active material mainly comprises a primary particle structure (i.e., a single-crystal particle structure). For example, more than 90%, optionally more than 92%, 94%, 96%, 98%, 99%, or even 100%, of the first positive electrode active material is a primary particle structure. In some embodiments, the second positive electrode active material mainly comprises a primary particle structure (i.e., a single-crystal particle structure). For example, more than 90%, optionally more than 92%, 94%, 96%, 98%, 99%, or even 100%, of the second positive electrode active material is a primary particle structure. In some embodiments, the third positive electrode active material mainly comprises a secondary particle structure (i.e., an aggregated particle structure). For example, more than 90%, optionally more than 92%, 94%, 96%, 98%, 99%, or even 100%, of the third positive electrode active material is a secondary particle structure.

[0072] Typically, primary particles have fewer lattice defects, smoother crystal surfaces, and higher compaction density. However, using only primary particles can result in an overly dense packing, which hinders both moisture drainage and electrolyte wetting, potentially leading to poor charge / discharge rate performance. In the positive electrode active material composition of this application, by combining primary and secondary particles, the positive electrode sheet can achieve both high compaction density and low moisture content, allowing the secondary battery to simultaneously achieve both high energy density and good rate performance.

[0073] In some embodiments, the morphology of the first positive electrode active material includes a spherical or near-spherical shape. In some embodiments, the morphology of the second positive electrode active material includes a spherical or near-spherical shape. In some embodiments, the morphology of the third positive electrode active material includes a spherical or near-spherical shape. "Near-spherical" means that the particle shape is substantially spherical, or the particle's aspect ratio is close to 1, for example, not greater than 1.3, optionally not greater than 1.2.

[0074] When the morphology of the positive electrode active material is spherical or near-spherical, it can have a better sliding effect, fill the gaps between particles in time, and increase the compaction density of the positive electrode sheet.

[0075] In some embodiments, the positive electrode active material composition includes a first positive electrode active material, a second positive electrode active material, and a third positive electrode active material, wherein the volume average particle size Dv50 of the first positive electrode active material is A1 μm, 0.2 ≤ A1 ≤ 0.8; the volume average particle size Dv50 of the second positive electrode active material is A2 μm, 1.0 ≤ A2 ≤ 2.5; and the volume average particle size Dv50 of the third positive electrode active material is A3 μm, 3.0 ≤ A3 ≤ 6.0; 4 ≤ A3 / A1 ≤ 20, optionally, 5 ≤ A3 / A1 ≤ 15; 0.6≤A3 / A2≤6.0, optionally, 2.0≤A3 / A2≤4.0; 1.5≤A2 / A1≤7.5, optionally, 1.8≤A2 / A1≤6.5; based on the total mass of the positive electrode active material composition as 100%, the mass percentage content w1 of the first positive electrode active material is 60%-80%, the mass percentage content w2 of the second positive electrode active material is 10%-40%, and the mass percentage content w3 of the third positive electrode active material is 7%-15%; 5≤w1 / w3≤11, optionally, 6≤w1 / w3≤9. In the positive electrode active material composition of this application, by rationally matching the particle size and mass content of the first positive electrode active material, the second positive electrode active material and the third positive electrode active material, the synergistic effect between the three positive electrode active materials with different particle sizes can be better utilized. As a result, the positive electrode sheet has both high compaction density and low moisture content, and the positive electrode sheet also has good ion and electron transport performance. The resulting battery can simultaneously achieve high safety performance, high energy density and good electrochemical performance.

[0076] In this application, the volume average particle size Dv50 of the material has a well-known meaning in the art, representing the particle size corresponding to a cumulative volume distribution percentage of 50%, which can be determined using instruments and methods known in the art. For example, it can be determined with reference to GB / T 19077-2016 and ISO 13320:2009. An exemplary test method includes the following steps: adding an appropriate amount of the sample to be tested (e.g., the sample concentration ensures that the opacity is between 8% and 12%) to 20 ml of deionized water and sonicating for 5 min (e.g., ultrasonic frequency 53 kHz, ultrasonic power 120 W) to completely disperse the sample, and then determining it according to GB / T19077-2016 and ISO 13320:2009. The testing instrument can be a laser particle size analyzer, such as the MasterSizer 2000 laser particle size analyzer from Malvern Instruments Ltd., UK.

[0077] Aqueous cathode slurry

[0078] The second aspect of this application provides an aqueous positive electrode slurry, comprising a solid component and a solvent water, wherein the solid component comprises an aqueous binder and a positive electrode active material composition of any embodiment of the first aspect of this application.

[0079] This application does not impose any particular limitation on the type of water-based adhesive, which can be selected according to actual needs. In some embodiments, the water-based adhesive includes, but is not limited to, at least one of acrylonitrile copolymers, polyethyleneimine (PEI), polyacrylic acid (PAA), polymethacrylic acid (PMAA), polyacrylamide (PAM), polyethylene oxide (PEO), polyvinyl alcohol (PVA), sodium alginate (SA), carboxymethyl chitosan (CMCS), and sodium carboxymethyl cellulose (CMC). As an example, the acrylonitrile copolymers include, but are not limited to, at least one of LA133 and LA132.

[0080] In some embodiments, the mass percentage of the aqueous binder may be 0.5%-5% based on the total mass of the solid components.

[0081] In some embodiments, the mass percentage of the positive electrode active material composition may be 93%-99% based on the total mass of the solid components.

[0082] In some embodiments, the solid component may optionally include a conductive agent. As an example, the conductive agent may include, but is not limited to, at least one of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, carbon nanofibers, and vapor-grown graphite tubes (VGGT).

[0083] Optionally, the conductive agent may include vapor-grown graphite tubes (VGGTs), which can improve the distribution of aqueous binders and increase the cohesion of the coating, thereby improving the flexibility of the positive electrode sheet.

[0084] Optionally, the mass percentage of the conductive agent can be 0.5%-2% based on the total mass of the solid components.

[0085] In some embodiments, the aqueous positive electrode slurry may optionally include other additives, such as plasticizers, to improve the flexibility of the positive electrode sheet. As an example, the plasticizer may include, but is not limited to, at least one of dimethyl phthalate, diethyl phthalate, dibutyl phthalate, dimethyl carbonate, diethyl carbonate, and propylene carbonate.

[0086] The method for preparing the aqueous positive electrode slurry of this application is well known. In some embodiments, the positive electrode active material composition, aqueous binder, optional conductive agent, and any other components can be dispersed in a solvent of water and stirred until homogeneous to form the slurry. There are no particular restrictions on the order of addition of the materials; they can be added simultaneously or in batches.

[0087] Positive electrode sheet

[0088] The third aspect of this application provides a positive electrode sheet, including a positive current collector and a positive electrode film layer disposed on the positive current collector, wherein the positive electrode film layer includes an aqueous binder and a positive electrode active material composition of the first aspect of this application, or is formed by drying an aqueous positive electrode slurry of the second aspect of this application.

[0089] The positive electrode sheet of this application can have a high compaction density while having a low moisture content. The positive electrode sheet of this application can also have good ion and electron transport performance, so the battery assembled from it can simultaneously achieve high safety performance, high energy density and good electrochemical performance.

[0090] In some embodiments, the positive electrode film layer may be formed by coating the above-mentioned aqueous positive electrode slurry onto the positive electrode current collector and then performing processes such as drying and cold pressing. The positive electrode current collector has two surfaces opposite each other in its thickness direction, and the positive electrode film layer is disposed on either or both of the two opposite surfaces of the positive electrode current collector.

[0091] In some embodiments, the thickness of the positive electrode film is not specifically limited, for example, it can be 50μm-500μm.

[0092] In this application, the thickness of the positive electrode film layer has a meaning known in the art and can be tested using methods known in the art, such as a micrometer. It should be noted that the thickness of the positive electrode film layer given in this application refers to the parameters of the positive electrode film layer on one side of the positive electrode current collector. When the positive electrode film layer is disposed on both sides of the positive electrode current collector, if the parameters of the positive electrode film layer on either side meet the requirements of this application, it is considered to fall within the protection scope of this application. Furthermore, the thickness of the positive electrode film layer in this application refers to the thickness of the positive electrode film layer after cold pressing and used for assembling the battery.

[0093] In some embodiments, the positive current collector may be a metal foil or a composite current collector. An example of a metal foil is aluminum foil. The composite current collector may include a polymer substrate and a metal layer formed on at least one surface of the polymer substrate. An example of a metal material may be at least one of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy. An example of a polymer substrate may be at least one of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).

[0094] In some embodiments, in the scanning electron microscope (SEM) cross-sectional image of the positive electrode film, the longest diagonal length of the first positive electrode active material particle is a1 μm, 0.2≤a1≤1.2, and the average center-to-center distance between adjacent first positive electrode active material particles is L1 μm, 0≤L1≤1.0.

[0095] In some embodiments, in the scanning electron microscope (SEM) cross-sectional image of the positive electrode film, the longest diagonal length of the second positive electrode active material particle is a2μm, 1.5≤a2≤2.7, and the average center distance between adjacent second positive electrode active material particles is L2μm, 0.5≤L2≤2.5.

[0096] In some embodiments, in the scanning electron microscope (SEM) cross-sectional image of the positive electrode film, the longest diagonal length of the third positive electrode active material particle is a3 μm, 3.2≤a3≤8.0, and the average center-to-center distance between adjacent third positive electrode active material particles is L3 μm, 5.0≤L3≤80.0.

[0097] In this application, the average center-to-center distance between adjacent first positive electrode active material particles can be obtained through the following testing method: A positive electrode sheet coated on one side and cold-pressed (if it is a double-sided coated positive electrode sheet, the positive electrode film layer on one side can be wiped off first using water or organic solvent) is punched into 2cm × 2cm samples for testing; during testing, the center-to-center distance between adjacent first positive electrode active material particles is counted and averaged in the scanning electron microscope (SEM) cross-section (perpendicular to the positive electrode current collector) image of the positive electrode film layer of the sample. Multiple samples (e.g., more than 5) can be randomly selected and punched from the effective area of ​​the positive electrode sheet for testing, and the average value of the results is taken, thereby improving the accuracy of the test results.

[0098] The average center-to-center distance between adjacent second positive electrode active material particles and the average center-to-center distance between adjacent third positive electrode active material particles can be obtained using a similar method.

[0099] It should be noted that the above tests on the positive electrode sheet can be conducted by sampling during the battery manufacturing process or by sampling from a pre-prepared secondary battery. As an example, when the test samples are taken from a pre-prepared secondary battery, the sampling can be performed as follows:

[0100] Discharge the secondary battery (for safety reasons, the battery is usually fully discharged); after removing the battery, take out the positive electrode and soak it in dimethyl carbonate (DMC) for a certain period of time (e.g., 2-10 hours); then take out the positive electrode and dry it at a certain temperature and time (e.g., 60℃, 4h), and then take out the positive electrode.

[0101] Furthermore, the test method provided in this application (the longest diagonal length of the particle and the average center-to-center distance between adjacent particles) is for the positive electrode film layer on one side of the positive electrode current collector. When the positive electrode film layer is disposed on both sides of the positive electrode current collector, if the test result of the positive electrode film layer on either side meets the requirements of this application, it is considered to fall within the protection scope of this application.

[0102] In some embodiments, the compaction density of the positive electrode sheet can be ≥2.50 g / cm³. 3 ≥2.52g / cm 3 ≥2.53g / cm 3 ≥2.54g / cm 3 ≥2.55g / cm 3 ≥2.56g / cm 3 ≥2.57g / cm 3 or ≥2.58g / cm 3In this application, the compaction density of the positive electrode sheet refers to the maximum value of the compaction density obtained before the positive electrode sheet is folded in half and breaks. An exemplary testing method includes the steps of: during cold pressing, adjusting the pressure of the roller press to continuously increase the compaction density of the positive electrode sheet until the positive electrode sheet is folded in half and breaks. The maximum value of the compaction density obtained before the positive electrode sheet is folded in half and breaks is the compaction density of the positive electrode sheet of this application.

[0103] In some embodiments, the moisture content of the positive electrode sheet after vacuum drying at 90°C for 6 hours can be ≤400ppm, ≤390ppm, ≤380ppm, ≤370ppm, ≤365ppm, ≤360ppm, ≤358ppm, ≤354ppm, ≤352ppm, ≤354ppm, ≤350ppm, ≤344ppm, ≤340ppm, or ≤335ppm.

[0104] In this application, the moisture content of the positive electrode sheet after vacuum drying at 90°C for 6 hours can be tested as follows: Aqueous positive electrode slurry is coated onto the positive electrode current collector, and then placed in a vacuum oven in a drying room (dew point < -30°C) for vacuum drying at 90°C for 6 hours to obtain the dried positive electrode film layer; 0.6g-1g of powder sample is weighed from the dried positive electrode film layer (e.g., using a blade to scrape the powder for sampling) and placed in a moisture testing chamber to detect the moisture content. The moisture testing chamber is a Karl Fischer moisture analyzer, and the weighing instrument can be an electronic balance.

[0105] In some embodiments, the compaction density of the positive electrode sheet is ≥2.50 g / cm³. 3 Furthermore, the moisture content after vacuum drying at 90℃ for 6 hours is ≤400ppm. Optionally, the compacted density of the positive electrode sheet is ≥2.50g / cm³. 3 Furthermore, the moisture content after vacuum drying at 90℃ for 6 hours is ≤365ppm.

[0106] In this application, ppm represents mass concentration.

[0107] Secondary batteries

[0108] A fourth aspect of this application provides a secondary battery, including a positive electrode, a negative electrode, and an electrolyte. During the charging and discharging process of the secondary battery, active ions are inserted and extracted back and forth between the positive electrode and the negative electrode, and the electrolyte plays a role in conducting active ions between the positive electrode and the negative electrode.

[0109] [Positive electrode plate]

[0110] The positive electrode used in the secondary battery of this application is the positive electrode of the third aspect of the embodiments of this application.

[0111] [Negative electrode plate]

[0112] In some embodiments, the negative electrode sheet includes a negative current collector and a negative electrode film layer disposed on at least one surface of the negative current collector. For example, the negative current collector has two surfaces opposite each other in its thickness direction, and the negative electrode film layer is disposed on either or both of the two opposite surfaces of the negative current collector.

[0113] The negative electrode current collector can be a metal foil or a composite current collector. As an example of a metal foil, copper foil can be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include at least one of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy. As an example, the polymer material base layer may include at least one of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).

[0114] The negative electrode film typically comprises a negative electrode active material, an optional binder, an optional conductive agent, and other optional additives. The negative electrode film is typically formed by coating a negative electrode slurry onto a negative electrode current collector, followed by drying and cold pressing. The negative electrode slurry coating is typically formed by dispersing the negative electrode active material, an optional conductive agent, an optional binder, and other optional additives in a solvent and stirring until homogeneous. The solvent may be N-methylpyrrolidone (NMP) or water, but is not limited to these. As an example, the binder used for the negative electrode film may include at least one of styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, aqueous acrylic resins (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), and carboxymethyl chitosan (CMCS). As an example, the conductive agent used for the negative electrode film may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. Other optional additives may include thickeners (e.g., sodium carboxymethyl cellulose, CMC), PTC thermistor materials, etc.

[0115] The negative electrode active material can be any negative electrode active material known in the art for use in secondary batteries. As examples, the negative electrode active material may include at least one of natural graphite, artificial graphite, soft carbon, hard carbon, mesophase microcarbon spheres, silicon-based materials, tin-based materials, lithium titanate, Li-Sn alloy, Li-Sn-O alloy, and Li-Al alloy. Silicon-based materials may include at least one of elemental silicon, silicon oxide, silicon-carbon composite, silicon-nitrogen composite, and silicon alloy materials. Tin-based materials may include at least one of elemental tin, tin oxide, and tin alloy materials. This application is not limited to these materials; other conventionally known materials that can be used as negative electrode active materials for secondary batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0116] The negative electrode sheet of this application does not exclude other additional functional layers besides the negative electrode film layer. For example, in some embodiments, the negative electrode sheet of this application further includes a conductive undercoat layer (e.g., composed of a conductive agent and an adhesive) sandwiched between the negative electrode current collector and the negative electrode film layer and disposed on the surface of the negative electrode current collector. In other embodiments, the negative electrode sheet of this application further includes a protective layer covering the surface of the negative electrode film layer.

[0117] [Electrolytes]

[0118] This application does not impose specific limitations on the type of electrolyte, which can be selected according to requirements. For example, the electrolyte may include at least one of solid electrolytes and liquid electrolytes (i.e., electrolyte solutions).

[0119] In some embodiments, the electrolyte is an electrolyte solution comprising an electrolyte salt and a solvent. The types of electrolyte salt and solvent are not specifically limited and can be selected according to actual needs.

[0120] As an example, the electrolyte salt may include at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalate borate (LiDFOB), lithium dioxalate borate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorodioxalate phosphate (LiDFOP), and lithium tetrafluorooxalate phosphate (LiTFOP).

[0121] As an example, the solvent may include at least one of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butyl ester carbonate (BC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS), and diethyl sulfone (ESE).

[0122] In some embodiments, the electrolyte may optionally include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives capable of improving certain battery performance, such as additives improving battery overcharge performance, battery high-temperature performance, and battery low-temperature power performance. As an example, the additives may include, but are not limited to, at least one of vinylene carbonate (VC), fluoroethylene carbonate (FEC), and 1,3-propanesulfonate lactone (PS).

[0123] [Isolation membrane]

[0124] Secondary batteries using electrolytes, as well as some secondary batteries using solid electrolytes, also include a separator. The separator is disposed between the positive and negative electrodes, primarily serving to prevent short circuits between the positive and negative electrodes while allowing active ions to pass through. This application does not impose any particular limitation on the type of separator; any known porous separator with good chemical and mechanical stability can be selected.

[0125] In some embodiments, the material of the separator can be selected from one or more of glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film. When the separator is a multi-layer composite film, the materials of each layer may be the same or different.

[0126] In some embodiments, the positive electrode sheet, the multilayer composite separator, and the negative electrode sheet can be fabricated into an electrode assembly using a winding process or a stacking process.

[0127] In some embodiments, the secondary battery may include an outer packaging. This outer packaging may be used to encapsulate the electrode assembly and electrolyte described above.

[0128] In some embodiments, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell. The outer packaging of the secondary battery can also be a soft pack, such as a pouch. The material of the soft pack can be plastic, such as at least one of polypropylene (PP), polybutylene terephthalate (PBT), and polybutylene succinate (PBS).

[0129] This application does not impose any particular limitation on the shape of the secondary battery; it can be cylindrical, square, or any other arbitrary shape. Figure 1 This is an example of a square-structured secondary battery 5.

[0130] In some embodiments, such as Figure 2 As shown, the outer packaging may include a housing 51 and a cover 53. The housing 51 may include a base plate and side plates connected to the base plate, the base plate and side plates forming a receiving cavity. The housing 51 has an opening communicating with the receiving cavity, and the cover 53 is used to cover the opening to close the receiving cavity. A positive electrode, a negative electrode, and a separator may be formed into an electrode assembly 52 by a winding process or a stacking process. The electrode assembly 52 is encapsulated in the receiving cavity. Electrolyte is immersed in the electrode assembly 52. ​​The secondary battery 5 may contain one or more electrode assemblies 52, which can be adjusted according to requirements.

[0131] In some embodiments of this application, the secondary battery according to this application can be assembled into a battery module. The number of secondary batteries contained in the battery module can be multiple, and the specific number can be adjusted according to the application and capacity of the battery module.

[0132] Figure 3 This is a schematic diagram of battery module 4 as an example. Figure 3 As shown, in battery module 4, multiple secondary batteries 5 can be arranged sequentially along the length of battery module 4. Of course, they can also be arranged in any other manner. Furthermore, these multiple secondary batteries 5 can be fixed in place using fasteners.

[0133] Optionally, the battery module 4 may also include a housing with a receiving space in which a plurality of secondary batteries 5 are received.

[0134] In some embodiments, the battery modules described above can also be assembled into a battery pack, and the number of battery modules contained in the battery pack can be adjusted according to the application and capacity of the battery pack.

[0135] Figure 4 and Figure 5 This is a schematic diagram of battery pack 1 as an example. Figure 4 and Figure 5As shown, the battery pack 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box includes an upper body 2 and a lower body 3. The upper body 2 covers the lower body 3, forming a closed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the battery box.

[0136] The method for preparing the secondary battery described in this application is well known. In some embodiments, a positive electrode, a separator, a negative electrode, and an electrolyte can be assembled to form a secondary battery. As an example, the positive electrode, separator, and negative electrode can be formed into an electrode assembly through a winding or stacking process. The electrode assembly is then placed in an outer packaging, dried, and injected with an electrolyte. After vacuum sealing, settling, formation, and shaping, a secondary battery is obtained.

[0137] Electrical appliances

[0138] A fifth aspect of this application provides an electrical device. The electrical device includes at least one of the secondary battery, battery module, or battery pack described in this application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device or as an energy storage unit for the electrical device. The electrical device may be, but is not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.

[0139] The electrical device can be equipped with a secondary battery, battery module, or battery pack according to its usage requirements.

[0140] Figure 6 This is a schematic diagram of an example electrical device. The device could be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the device's requirements for high power and high energy density, a battery pack or battery module can be used.

[0141] Another example of an electrical device could be a mobile phone, tablet, or laptop. These devices typically require a slim and lightweight design and can use rechargeable batteries as their power source.

[0142] Example

[0143] The following embodiments describe the disclosure of this application in more detail. These embodiments are merely illustrative, as various modifications and variations will be apparent to those skilled in the art within the scope of the disclosure of this application. Unless otherwise stated, all parts, percentages, and ratios reported in the following embodiments are based on mass, and all reagents used in the embodiments are commercially available or synthesized by conventional methods and can be used directly without further processing, and the instruments used in the embodiments are commercially available.

[0144] Example 1

[0145] Preparation of positive electrode sheet

[0146] The first positive electrode active material LiFePO4 with a Dv50 of 0.4 μm, the second positive electrode active material LiFePO4 with a Dv50 of 1.5 μm, and the third positive electrode active material LiFePO4 with a Dv50 of 4 μm were mixed evenly in a mass ratio of 70:22:8 to obtain the positive electrode active material.

[0147] The above-mentioned positive electrode active material, conductive carbon black (Super P), aqueous binder LA-133 and polyethyleneimine 1:1 mixture were thoroughly mixed in an appropriate amount of deionized water at a mass ratio of 96:1:3 to form a positive electrode slurry with a solid content of 50%. The positive electrode slurry was uniformly coated on the surface of the positive electrode current collector aluminum foil, and then placed in a vacuum oven in a drying room (dew point < -30℃) and vacuum dried at 90℃ for 6 hours. After cold pressing, slitting and other processes, the positive electrode sheet was obtained.

[0148] The moisture content of the positive electrode sheet can be tested using the following method:

[0149] Weigh 0.6g-1g of powder sample from the positive electrode film layer after vacuum drying at 90℃ for 6 hours and before cold pressing. Then, place the powder sample in a moisture testing chamber to determine its moisture content. The moisture testing chamber is a Karl Fischer moisture analyzer, and the weighing instrument can be an electronic balance.

[0150] The compaction density of the positive electrode sheet can be tested as follows: During the cold pressing process, the pressure of the roller press is adjusted to continuously increase the compaction density of the positive electrode sheet until it breaks when folded in half. The maximum compaction density obtained before the positive electrode sheet breaks is the compaction density of the positive electrode sheet of this application. The compaction density of the positive electrode sheet = mass of the positive electrode film layer / volume of the positive electrode film layer. Here, the mass and volume of the positive electrode film layer refer to the parameters of the positive electrode film layer on one side of the positive electrode current collector.

[0151] Preparation of negative electrode sheet

[0152] Artificial graphite (anode active material), carbon black (Super P) (conductive agent), styrene-butadiene rubber (SBR) (binder), and sodium carboxymethyl cellulose (CMC) (thickener) were mixed thoroughly in an appropriate amount of deionized water at a mass ratio of 96.2:0.8:0.8:1.2 to form a negative electrode slurry with a solid content of 30%. The negative electrode slurry was uniformly coated on the surface of the copper foil (anode current collector), dried at 85°C, and then cold-pressed and slit to obtain the negative electrode sheet.

[0153] Preparation of electrolyte

[0154] In an argon atmosphere glove box (H2O < 0.1 ppm, O2 < 0.1 ppm), ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were mixed at a volume ratio of 3:7 to obtain an organic solvent; LiPF6 was uniformly dissolved in the above organic solvent to obtain an electrolyte, wherein the mass fraction of LiPF6 was 12.5%.

[0155] Preparation of the separating membrane

[0156] A ceramic slurry is coated on one surface of a PE porous membrane and dried to obtain a separation membrane, wherein the thickness of the ceramic coating is 2 μm.

[0157] Preparation of secondary batteries

[0158] The positive electrode, separator, and negative electrode are stacked and wound in sequence to obtain an electrode assembly. The electrode assembly is placed in an outer aluminum shell, baked at 80°C, and then the electrolyte is added. After vacuum sealing, settling, formation, and shaping, a secondary battery is obtained.

[0159] Examples 2-14 and Comparative Examples 1-10

[0160] The preparation method of the secondary battery is similar to that in Example 1, except that the preparation parameters of the positive electrode active material are different, as detailed in Table 1.

[0161] Test section

[0162] At 25°C, the secondary batteries prepared in each embodiment and comparative example were charged at a constant current of 0.33C to 3.65V, then charged at a constant voltage to 0.05C. After resting for 5 minutes, the charging capacity at this point was recorded, which is the 0.33C charging capacity. After resting for 5 minutes, the secondary batteries were discharged at a constant current of 0.33C to 2.5V. After resting for 30 minutes, the secondary batteries were charged at a constant current of 2C to 3.65V, then charged at a constant voltage to 0.05C. After resting for 5 minutes, the charging capacity at this point was recorded, which is the 2C charging capacity. The rate performance of the secondary batteries is characterized by the 2C / 0.33C charging capacity retention rate, where a higher 2C / 0.33C charging capacity retention rate indicates better rate performance of the secondary batteries.

[0163] Secondary battery 2C / 0.33C charging capacity retention rate (%) = (2C charging capacity / 0.33C charging capacity) × 100%.

[0164] The test results of Examples 1-14 and Comparative Examples 1-10 are shown in Table 1.

[0165] Table 1

[0166]

[0167]

[0168] As can be seen from the test results in Table 1, by combining the first, second, and third positive electrode active materials with different particle sizes, this application achieves a synergistic effect among the three positive electrode active materials with different particle sizes. As a result, the positive electrode sheet has both high compaction density and low moisture content, and the positive electrode sheet also has good ion and electron transport performance. Therefore, the secondary battery obtained in this way also has good rate performance. Figure 7 and Figure 8 These are scanning electron microscope cross-sectional images of the positive electrode film layer of Example 1 at different magnifications. Figure 7 and Figure 8 It can be seen that the positive electrode sheet using the positive active material composition of this application can have a high compaction density.

[0169] The test results of Comparative Examples 1-3 show that when the first, second, and third positive electrode active materials are used alone, none of them can make the positive electrode sheet have both high compaction density and low moisture content, and the rate performance of the resulting secondary battery is also poor.

[0170] The test results of Comparative Examples 4-6 show that even when any two of the first, second, and third positive electrode active materials are combined, it is still impossible to achieve both high compaction density and low moisture content in the positive electrode sheet, and the rate performance of the resulting secondary batteries is also poor.

[0171] The test results of Comparative Examples 7-8 show that when the particle size of the first positive electrode active material is too small or too large, the positive electrode sheet cannot achieve both high compaction density and low moisture content, resulting in poor rate performance of the secondary battery. The possible reasons are: when the particle size of the first positive electrode active material is too small, the third positive electrode active material cannot effectively reduce the dense packing state formed by the first positive electrode active material, leading to insufficient moisture evaporation channels in the slurry coating, high moisture content in the positive electrode sheet, and poor electrolyte wettability, resulting in poor rate performance of the secondary battery. When the particle size of the first positive electrode active material is too large, it is difficult to form a dense packing effect, resulting in low compaction density of the positive electrode sheet, small contact area between the positive electrode active material particles, fewer electron conduction channels, and high internal resistance of the battery, also leading to poor rate performance of the secondary battery.

[0172] The test results of Comparative Example 9 show that when the particle size of the second positive electrode active material is too small, the positive electrode sheet cannot achieve both high compaction density and low moisture content, resulting in poor rate performance of the secondary battery. A possible reason is that when the particle size of the second positive electrode active material is too small, it cannot provide adequate lubrication, leading to insufficient moisture evaporation channels in the slurry coating, higher moisture content in the positive electrode sheet, and consequently, poor rate performance of the secondary battery.

[0173] The test results of Comparative Example 10 show that when the particle size of the third positive electrode active material is too large, the positive electrode sheet cannot achieve both high compaction density and low moisture content, resulting in poor rate performance of the secondary battery. This may be because a large particle size makes it difficult to form a dense packing effect, leading to a lower compaction density of the positive electrode sheet, smaller contact area between the particles, fewer electron conduction channels, and higher internal resistance, thus resulting in poor rate performance of the secondary battery. Furthermore, a large particle size also worsens the uniformity of slurry dispersion and coating thickness, resulting in a rougher coating surface and a lower positive electrode sheet yield.

[0174] The test results from Examples 1-12 and 13-14 also show that when the ratio w1 / w3 of the content of the first positive electrode active material to the content of the third positive electrode active material is further controlled within a suitable range, the synergistic effect between the third positive electrode active material and the first positive electrode active material can be better utilized. Consequently, the positive electrode sheet can have a higher compaction density while having a lower moisture content, and the positive electrode sheet also has good ion and electron transport performance. Therefore, the resulting secondary battery can have better rate performance. Optionally, 5 ≤ w1 / w3 ≤ 11. Further, 6 ≤ w1 / w3 ≤ 9.

[0175] The test results from Examples 1-12 also show that when the particle sizes of the first, second, and third positive electrode active materials are further controlled within a suitable range (5≤A3 / A1≤15, 2.0≤A3 / A2≤4.0, 1.8≤A2 / A1≤6.5), the synergistic effect between the three positive electrode active materials with different particle sizes can be better utilized. As a result, the positive electrode sheet can have a higher compaction density while having a further reduced moisture content, and the positive electrode sheet also has good ion and electron transport performance. The resulting secondary battery can have better rate performance.

[0176] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.

Claims

1. A positive electrode active material composition, characterized in that, It includes a first positive electrode active material, a second positive electrode active material, and a third positive electrode active material, wherein the first positive electrode active material, the second positive electrode active material, and the third positive electrode active material are all lithium phosphates with an olivine structure and their modified compounds. in, The volume average particle size Dv50 of the first positive electrode active material is A1 μm, 0.2≤A1≤0.8; The volume average particle size Dv50 of the second positive electrode active material is A2 μm, where 1.0 ≤ A2 ≤ 2.5; The volume average particle size Dv50 of the third positive electrode active material is A3 μm, where 3.0 ≤ A3 ≤ 6.0; Based on the total mass of the positive electrode active material composition being 100%, the mass percentage w1 of the first positive electrode active material is 60%-80%, the mass percentage w2 of the second positive electrode active material is 10%-32%, and the mass percentage w3 of the third positive electrode active material is 7%-15%.

2. The positive electrode active material composition according to claim 1, characterized in that, 4≤A3 / A1≤20; and / or, 1.6 ≤ A3 / A2 ≤ 6.0; and / or, 1.5≤A2 / A1≤7.

5.

3. The positive electrode active material composition according to claim 2, characterized in that, 5≤A3 / A1≤15; and / or, 2.0 ≤ A3 / A2 ≤ 4.0; and / or, 1.8≤A2 / A1≤6.

5.

4. The positive electrode active material composition according to claim 1, characterized in that, 5≤w1 / w3≤11.

5. The positive electrode active material composition according to claim 2, characterized in that, 6≤w1 / w3≤9.

6. The positive electrode active material composition according to any one of claims 1-5, characterized in that, The positive electrode active material composition satisfies at least one of the following conditions (1) to (8): (1) The first positive electrode active material, the second positive electrode active material and the third positive electrode active material each independently include at least one of lithium iron phosphate, lithium manganese phosphate, lithium cobalt phosphate, lithium iron manganese phosphate and their respective modified compounds. (2) The first positive electrode active material, the second positive electrode active material, and the third positive electrode active material are made of the same material. (3) A conductive carbon layer is disposed on the surface of the first positive electrode active material. (4) A conductive carbon layer is disposed on the surface of the second positive electrode active material. (5) A conductive carbon layer is disposed on the surface of the third positive electrode active material. (6) More than 90% of the first positive electrode active material is a primary particle structure. (7) More than 90% of the second positive electrode active material is a primary particle structure. (8) More than 90% of the third positive electrode active material is a secondary particle structure.

7. An aqueous positive electrode slurry, comprising a solid component and a solvent water, wherein, The solid component includes an aqueous binder and a positive electrode active material composition according to any one of claims 1-6.

8. The aqueous positive electrode slurry according to claim 7, characterized in that, The water-based binder includes at least one of acrylonitrile copolymer, polyethyleneimine, polyacrylic acid, polymethacrylic acid, polyacrylamide, polyethylene oxide, polyvinyl alcohol, sodium alginate, carboxymethyl chitosan, and sodium carboxymethyl cellulose.

9. A positive electrode sheet, comprising a positive current collector and a positive electrode film layer disposed on the positive current collector, characterized in that, The positive electrode film layer comprises an aqueous binder and a positive electrode active material composition according to any one of claims 1-6, or the positive electrode film layer is formed by drying the aqueous positive electrode slurry according to claim 7 or 8.

10. The positive electrode sheet according to claim 9, characterized in that, In the scanning electron microscope cross-sectional image of the positive electrode film, The longest diagonal length of the first positive electrode active material particle is a1 μm, 0.2≤a1≤1.2, and the average center distance between adjacent first positive electrode active material particles is L1 μm, 0≤L1≤1.0; The longest diagonal length of the second positive electrode active material particle is a2 μm, 1.5≤a2≤2.7, and the average center distance between adjacent second positive electrode active material particles is L2 μm, 0.5≤L2≤2.5; The longest diagonal length of the third positive electrode active material particle is a3 μm, 3.2≤a3≤8.0, and the average center distance between adjacent third positive electrode active material particles is L3 μm, 5.0≤L3≤80.

0.

11. The positive electrode sheet according to claim 9 or 10, characterized in that, The compaction density of the positive electrode sheet is ≥2.50 g / cm³. 3 Furthermore, the moisture content after vacuum drying at 90℃ for 6 hours is ≤400ppm.

12. The positive electrode sheet according to claim 11, characterized in that, The moisture content of the positive electrode sheet after vacuum drying at 90°C for 6 hours is ≤365ppm.

13. A secondary battery comprising a positive electrode sheet according to any one of claims 9-12.

14. An electrical device comprising a secondary battery according to claim 13.

Citation Information

Patent Citations

  • Lithium manganese oxide positive active material and lithium ion secondary battery including the same

    CN103367738A

  • Non-aqueous electrolyte secondary battery positive electrode and non-aqueous electrolyte secondary battery

    CN103782417A

  • Preparation method of positive water slurry, positive pole piece of lithium battery and lithium battery

    CN107275574A

  • Positive-electrode active material, positive electrode, battery, battery pack, electronic device, electric vehicle, electricity storage device, and electric power system

    CN108431998A

  • Lithium ion battery water-based positive electrode slurry, preparation method thereof and lithium ion battery

    CN109301244A